(untitled) (Advances in Systems Science and Applications, 2020)
The paper presents a study of impasse (singular) points of autonomous quasi-linear constrained differential systems, also called differential-algebraic equations. The interest in such systems is motivated by their applications in various problems of pure and applied mathematics, including control theory, biology, and electric engineering. Local normal forms of such systems in a neighborhood of their impasse points are established.